The RELATIONSHIP OF PREGNAN WOMEN’S CHARACTERISTICS TO THEIR PERCEPTION OF THE MCH BOOK, BENDA KEREP UB-VILLAGE, ARGASUNYA VILLAGE, CIREBON CITY - vianty sari; Nurhasanah Nurhasanah (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2021)
in Indonesia, breast cancer is the second leading cause of death for women after cervical cancer. Based on data from the Cirebon City Health Office in 2015, the number of maternal deaths was 4/5400 live births, the number of infant deaths was 25/5455 live births, and the number of under-five deaths was 8/5378 live births. Aspects of maternal and child health can be seen from several indicators of achievement, one of which is Infant Immunization. In 2015, of 22 urban villages in the city of Cirebon, there was only one village that had not reached the target, namely in the Argasunya village. Meanwhile, the coverage of deliveries by health workers in Argasunya was 52.64% and the highest delivery assistance by traditional birth attendants in the city of cirebon was in Argasunya Village at 4.63%. The purpose of this study was to determine the relationship between characteristics and perceptions of pregnant women on the MCH Handbook. This study used a cross sectional design. The population of all pregnant women in Benda Kerep Sub-Village, Argasunya Village, Cirebon City. Sampling used total sampling. The data taken were primary data obtained through questionnaires given to 23 pregnant women. The correlation test used Chi-Square. The results of the study showed that the majority of pregnant women had a bad perception of the MCH handbook (69.56%), were aged 20-35 (87%), graduated from elementary school (78%), were with 14-27 weeks in gestation (48%), and had a plan to deliver at home (73.92%). Based on occupation, all pregnant women did not work (100%). There was no relationship between age and perception of the MCH handbook, between education and perception of the MCH handbook, between occupation and perception of the MCH handbook, and between planned place of delivery and perception of the MCH handbook.